Micro connector fabricated by micro process technology - Bhuiyan, Md. Moinul Islam; Unno, Toshinori; Yokoyama, Yoshihiko; Toriyama, Toshiyuki; Sugiyanta, Susumu (2000)
A fork - type micro connector with high aspect ratio and high - package density was fabricated using UV thick photoresist and Ni electroforming. A negative photoresist (THB - 138N) was used as a mold of Ni electroforming. The tips of plug terminal of the micro connector were formed as movable portions using Cu sacrificial layer etching. In order to make iinn contact and precise connection of the micro connector, two-step guidance was adopted. The size of the tenninal of fabricated micro connector was 50 p - thickness and 15 pm - width (minimum). The maximum aspect ratio of the fabricated micro connector is 3.3 and the terminal pitch is 80 pn. A contact ?&stance of approximately 50 & was obtained by using four - point probe method.